Occurrence of aspiration pneumonia in dysphagic children post video fluoroscopy - Lagos, Hellen Nataly Correia; Santos, Rosane Sampaio; Celli, Adriane; Abdulmassih, Edna Marcia Silva; Medeiros, Carlos Alberto do Amaral (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: The literature reports that when it comes of instrumental assessment of swallowing in children, undoubtedly, video fluoroscopy of swallow offers great advantages over the endoscopic study.Objective: Check the risk of aspiration pneumonia after the study of swallowing by video fluoroscopy, in children with dysphagia.Method: In a study of prospective cutting, participated 16 children aged between 6 months and 10 years, with an average of 5,2 years, referred for study of swallowing by video fluoroscopy. Were tested 4 consistencies, pudding, nectar, honey and liquid. The presences of signs and/or respiratory symptoms were evaluated pre and post study of deglutition by video fluoroscopy, through history and clinical exam. When necessary was asked chest x-ray.Results: Of 16 children, 5 didn't presented dysphagia. In 11 children the exam showed 4 with mild dysphagia, 2 moderate and 5 severe, as classification of OTT (1996) - Classification of severity of dysphagia to the video fluoroscopy. Of the 7 children who aspirated during the exam, only 1 presented respiratory symptoms after the deglutition study, but without signal of pneumonia to the physical examination.Conclusion: In the studied population there were no occurrences of aspiration pneumonia after the study of deglutition was performed by video fluoroscopy, despite the occurrence of aspiration during the exam in about 50% of cases.
Keywords: deglutition disorders; aspiration pneumonia; fluoroscopy